A new life time distribution with applications in reliability and environmental sciences. Issue 3 (3rd April 2021) - Abbas, Salman; Mohsin, Muhammad; Pilz, Jürgen
Abstract: This paper presents a new life time distribution developed by the generalization of the Length-Biased Exponential distribution. The addition of shape parameter to this distribution enhances its adaptability to model the life time data. Different structural properties like moments, quantile function and order statistics along with empirical study are presented. Several measures of reliability analysis are given. The expression of Réyni, q and Shannon entropies are also conferred. The model parameters are estimated by the maximum likelihood method. The application of the proposed model to three examples from different fields and its comparison with the existing models show the better performance whereas three different trends of hazard rate function by total time on test (TTT) plots show its vast implementation.